2011
DOI: 10.1002/mmng.201000017
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Late Permian - Jurassic radiolarian extinction rates: no evidence for an end-Triassic mass extinction

Abstract: The hypothesis that ocean acidification was a proximate trigger of the marine end‐Triassic mass extinction rests on the assumption that taxa that strongly invest in the secretion of calcium‐carbonate skeletons were significantly more affected by the crisis than other taxa. An argument against this hypothesis is the great extinction toll of radiolarians that has been reported from work on local sections. Radiolarians have siliceous tests and thus should be less affected by ocean acidification. We compiled taxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…The ocean acidification model predicts an increased extinction risk for taxa with an aragonite or high-Mg calcite skeletal mineralogy (Hautmann, 2004;Knoll et al, 2007;Hautmann et al, 2008a) and, thus, offers a possible explanation for the preferential extinction of reef communities, ammonoids, and aragonitic bivalves at the end of the Triassic (Hautmann et al, 2008a(Hautmann et al, , 2008b, which is in contrast to groups with such noncalcareous skeletons as radiolarians that had no significantly increased extinction risk (Kiessling and Danelian, 2011;Hönisch et al, 2012). Somewhat counterintuitively, taxa with massive or thick-shelled skeletons, including strongly ornamented forms, also appear to be at an elevated extinction risk, because decreased CaCO 3 saturation of seawater raises energy expenditure for biocalcification, which puts such taxa at a selective disadvantage (Hautmann, 2006;Knoll et al, 2007;Veron, 2008Veron, , 2011Kiessling and Simpson, 2011).…”
Section: Implications For the Causes Of Extinctionmentioning
confidence: 96%
See 1 more Smart Citation
“…The ocean acidification model predicts an increased extinction risk for taxa with an aragonite or high-Mg calcite skeletal mineralogy (Hautmann, 2004;Knoll et al, 2007;Hautmann et al, 2008a) and, thus, offers a possible explanation for the preferential extinction of reef communities, ammonoids, and aragonitic bivalves at the end of the Triassic (Hautmann et al, 2008a(Hautmann et al, , 2008b, which is in contrast to groups with such noncalcareous skeletons as radiolarians that had no significantly increased extinction risk (Kiessling and Danelian, 2011;Hönisch et al, 2012). Somewhat counterintuitively, taxa with massive or thick-shelled skeletons, including strongly ornamented forms, also appear to be at an elevated extinction risk, because decreased CaCO 3 saturation of seawater raises energy expenditure for biocalcification, which puts such taxa at a selective disadvantage (Hautmann, 2006;Knoll et al, 2007;Veron, 2008Veron, , 2011Kiessling and Simpson, 2011).…”
Section: Implications For the Causes Of Extinctionmentioning
confidence: 96%
“…Reduced CaCO 3 saturation of seawater due to oceanic uptake of volcanogenic CO 2 and SO 2 and concomitant decrease of seawater pH (ocean acidification) is the latest extinction model for the end-Triassic marine extinction (Hautmann, 2004), which has been intensively discussed in the last years (e.g., Galli et al, 2005;Berner and Beerling, 2007;van de Schootbrugge et al, 2007;Hautmann et al, 2008a;Kiessling et al, 2008;Č rne et al, 2011;Kiessling and Danelian, 2011;. The ocean acidification model predicts an increased extinction risk for taxa with an aragonite or high-Mg calcite skeletal mineralogy (Hautmann, 2004;Knoll et al, 2007;Hautmann et al, 2008a) and, thus, offers a possible explanation for the preferential extinction of reef communities, ammonoids, and aragonitic bivalves at the end of the Triassic (Hautmann et al, 2008a(Hautmann et al, , 2008b, which is in contrast to groups with such noncalcareous skeletons as radiolarians that had no significantly increased extinction risk (Kiessling and Danelian, 2011;Hönisch et al, 2012).…”
Section: Implications For the Causes Of Extinctionmentioning
confidence: 99%
“…Because of the nature of its extraordinary fossil record (very large number of individuals, relatively constant and widespread biogeographic and sedimentary regions, organisms with a wide variety of biological properties or ecological niches found together in the same samples), marine micropaleontology offers a unique resource for paleobiology (Lipps 1981;Lazarus 2011). Nonetheless, only recently have macroevolutionary studies begun to exploit this potential by using large, global data sets (Rabosky and Sorhannus 2009;Kaminski et al 2010;Liow et al 2010;Kiessling and Danelian 2011;Lloyd et al 2011;Ezard et al 2011), thanks to the creation and the use of fossil occurrence databases such as the Paleobiology Database (Alroy et al 2001), mostly for Mesozoic microfossil data, and the Neptune database Spencer-Cervato 1999), the latter containing much of the (largely Cenozoic) microfossil occurrence data published in the context of the DSDP/ ODP drilling campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the much-studied early Toarcian Oceanic Anoxic Event (Jenkyns 2010) and the related second-order extinction is said to be manifested in elevated radiolarian turnover. Hori (1997) described a Toarcian radiolarian event from bedded cherts of Japan, but this has not been confirmed from elsewhere, and a distinct extinction peak is not evident at the stage level (Kiessling and Danelian 2011).…”
Section: Introductionmentioning
confidence: 98%
“…However, the radiolarian range data of Sepkoski (2002) are rather outdated and some radiolarian workers maintain that the group was seriously hit by the end-Triassic event (Carter and Hori 2005). A recent sampling-standardized analysis of the radiolarian fossil record from the Late Permian to Late Jurassic concluded that although Rhaetian extinction rates were higher than in Sepkoski's compendium, there is no evidence for an end-Triassic mass extinction (Kiessling and Danelian 2011). Instead, the end-Triassic extinctions fall within the background of generally elevated Triassic extinction rates.…”
Section: Introductionmentioning
confidence: 99%